SISTEM SURAT-MENYURAT BERBASIS WEB DI KANTOR DESA BALE MUSARA - Zainal Zainal; Amna Amna; Hendri Syahputra (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2022)
Mailing is one of the Web systems that is now widely used in modern administrative systems. The correspondence system is a system related to administration that virtually concentrates the components of an organization, where data, information, and communication are made through telecommunication media with the aim of building a system that is able to accommodate each element. This correspondence system is built using the SDLC (Software Development Life Cycle) method with the Waterfall Model software development technique. For the use of the correspondence system, a study was conducted entitled "Web-Based Correspondence System at the Bale Musara Village Office". This research uses quantitative research methods. The results of testing the Web-based Correspondence System are in accordance with the system proposed and expected by system users, especially for village operators and secretaries. Based on the research and creation of the system that has been carried out, there are several conclusions, namely the Making of a Correspondence Information System at the Bale Musara Village Office can be used to facilitate the work of village officials.